Salinity reduces bacterial diversity, but increases network complexity in Tibetan Plateau lakes - Ji, Mukan; Kong, Weidong; Yue, Linyan; Wang, Junbo; Deng, Ye; Zhu, Liping (FEMS microbiology ecology, 2019)
ABSTRACT Salinity is one of the most important environmental factors influencing bacterial plankton communities in lake waters, while its influence on bacterial interactions has been less explored. Here, we investigated the influence of salinity on the bacterial diversity, interactions and community structure in Tibetan Plateau lakes. Our results revealed that saline lakes (salinity between 0.5 and 50 g/L) harboured similar or even higher bacterial diversity compared with freshwater lakes (< 0.5 g/L), while hyper-saline lakes (> 50 g/L) exhibited the lowest diversity. Network analysis demonstrated that hyper-saline lakes exhibited the highest network complexity, with higher total correlation numbers (particularly the negative correlations), but lower network module numbers than freshwater and saline lakes. Furthermore, salinity dominantly explained the bacterial community structure variations in saline lakes, while those in freshwater and hyper-saline lakes were predominately explained by water temperature and geospatial distance, respectively. The core operational taxonomic units (OTUs), which were ubiquitously present in all lakes, were less sensitive to enhancing salinity than the indicative OTUs whose presence was dependent on lake type. Our findings offer a new understanding of how salinity influences bacterial community in plateau lakes. Enhancing salinity significantly reduces bacterial richness and diversity, but increases network complexity, and substantially changes bacterial community structure in Tibetan Plateau lakes.